2020
DOI: 10.1670/17-079
|View full text |Cite
|
Sign up to set email alerts
|

Population Size and Dynamics of the Lima Leaf-Toed Gecko, Phyllodactylus sentosus, in One of Its Last Refuges

Abstract: The Peruvian endemic Lima Leaf-Toed Gecko (Phyllodactylus sentosus) is a critically endangered species with just a few known localities of occurrence, which are isolated from each other, within Lima City and in the Ica region. During 1 yr, we carried out monthly evaluations to determine the influence of the environmental factors on the size and population dynamics of this species in the Huaca Pucllana, as this area maintains one of the largest populations in Lima. We took body measurements and reproductive dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…4 A). The populations at the extremes of the geographical distribution of this species show the lowest migration rates, while those among the four largest census population size 16 – 18 (San Marcos, Parque de Las Leyendas, Pucllana and Mateo Salado: Fig. 4 , see Supplementary Table S3 online) were slightly higher, but still lower than 0.4, with exception of the populations of San Marcos and Parque de Las Leyendas that showed a high bidirectional gene flow with migration values of 0.99 and 1 (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…4 A). The populations at the extremes of the geographical distribution of this species show the lowest migration rates, while those among the four largest census population size 16 – 18 (San Marcos, Parque de Las Leyendas, Pucllana and Mateo Salado: Fig. 4 , see Supplementary Table S3 online) were slightly higher, but still lower than 0.4, with exception of the populations of San Marcos and Parque de Las Leyendas that showed a high bidirectional gene flow with migration values of 0.99 and 1 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…1 ), which feature arid soil with scant vegetation and small rocks that resemble the natural habitat previous to human occupancy 11 . Nowadays, these areas are isolated from each other by completely urbanized areas in Lima, being estimated not to exceed the 500 adult individuals in huacas with the largest census population size 16 – 18 . Also, unlike other Phyllodactylus species, P. sentosus has low climbing abilities due to their toe structure, which reduces the probability of dispersion and escape from invasive local threats 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although capture has been widely used to estimate abundance, even recently (e.g. Kahn et al, 2019; Brown et al, 2020; Valdez et al, 2020), according to Cooch & White (2019), all the heterogeneity models in capture , except M bh , are not likelihood based. All eight Otis models can be modelled in program mark , with different estimators than used in capture .…”
Section: Methodsmentioning
confidence: 99%
“…Although CAPTURE has been widely used to estimate abundance, even recently (e.g. Kahn et al, 2019;Brown et al, 2020;Valdez et al, 2020), according to Cooch & White (2019), all the heterogeneity models in CAPTURE, except M bh , are not likelihood based.…”
Section: Abundancementioning
confidence: 99%
“…In addition, cities are at times the last remaining refuge for a species. A case in point is the Lima leaf-toed gecko (Phyllodactylus sentosus), a critically endangered species that is restricted to only several locations within the city of Lima, Peru (Valdez et al 2020). In contrast, cities may also be locations where previously undescribed species are discovered; for example, a new species of mud turtle (Kinosternon vogti) was recently identified in Puerto Vallarta, Mexico (López- Luna et al 2018), and a new species of leopard frog was found in New York City (Figure 1; Feinberg et al 2014).…”
mentioning
confidence: 99%